Relationship between learning styles and research morale among Iranian second grade high school students - Sarvestani, Mariam Shafiei; Abd Rahman, Fadzilah; Jahani, Jafar; Mousavipour, Rohollah (Human Resource Management Academic Research Society, 2019)
Consideration to the learning styles benefits students to participate more enthusiastically in the class activities and to be more confident in answering questions asked by the teacher. This study aimed to investigate the relationship between learning styles and research morale among students of the second grade high school in Shiraz, Iran. Population of the study included all students of the second grade high school in four areas of Shiraz in the academic year of 2015- 2016. A number of 345 students were selected using multi-stage cluster sampling method. Research tools included the Kolb’s learning style questionnaire and the research morale questionnaire by Mohammadsharifi (2013). The results were analyzed by SPSS and Lisrel Software’s. Results showed that the dominant learning style among the students was a convergent learning style. No difference was seen between research morale of male and female students. Among all learning styles, convergent and divergent styles had a significant association with research morale. Moreover, there was a significant multiple correlations between convergent, divergent, assimilation, and accommodative learning styles and research morale. The finding revealed that the two learning styles of convergent and divergent were stronger predictive of research morale. This study may confirm the role of learning styles in developing research morale and approve the hypothesis that in learning, both convergent and divergent styles should be considered.